2021
DOI: 10.1111/jce.14925
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of catheter ablation in patients with persistent atrial fibrillation guided by fragmented late‐gadolinium enhancement areas

Abstract: Background A computer simulation model has demonstrated that atrial fibrillation (AF) driver can be attached to heterogeneous fibrosis assessed by late gadolinium enhancement magnetic resonance imaging (LGE‐MRI). However, it has not been well elucidated in patients with persistent AF. The aim of this study was to investigate whether radiofrequency (RF) applications in the fragmented LGE area (FLA) could terminate AF or convert it to atrial tachycardia (AT) and improve the rhythm outcome. Methods A total of 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…To more sensitively detect weak LGE areas, we used the same protocol as in our previous study 9 . The 3D visualization method for the LGE was as follows.…”
Section: Methodsmentioning
confidence: 99%
“…To more sensitively detect weak LGE areas, we used the same protocol as in our previous study 9 . The 3D visualization method for the LGE was as follows.…”
Section: Methodsmentioning
confidence: 99%
“…To detect normal/mild LGE areas more sensitively, we used the same protocol as in our previous study. 12 The 3D visualization method for the LGE was as follows. First, the LA in the LGE‐MRI was semi‐manually segmented by contouring the borders between the endocardium and epicardium of the atrium, including the PVs, with reference to the CE‐MRA.…”
Section: Methodsmentioning
confidence: 99%
“…To detect normal/mild LGE areas more sensitively, we used the same protocol as in our previous study 12 . The 3D visualization method for the LGE was as follows.…”
Section: Methodsmentioning
confidence: 99%
“…In a non-randomized study, AF organization and termination was demonstrated in a cohort of 31 persistent AF patients with a low rate of arrhythmia recurrence during follow-up in this group. 79 …”
Section: Section 3: Using Advanced Imaging Techniques To Guide Ablation Proceduresmentioning
confidence: 99%